177k views
4 votes
y = x + 2 2x - y = -4 Solve the system of equations using substitution. A) (-2,-4) B) (-2,0) C) (-6,-4) D) (-6,8)

User Tekill
by
5.0k points

1 Answer

6 votes

For this case we must solve the following system of equations:


y = x + 2\\2x-y = -4

So, we substitute the first equation in the second one:


2x- (x + 2) = - 4

We consider by law of signs of multiplication that:


- * + = -\\2x-x-2 = -4\\x-2 = -4\\x = -4 + 2

Different signs are subtracted and the sign of the major is placed:


x = -2

We look for the value of the variable "y":


y = -2 + 2\\y = 0

Thus, the solution of the system is given by:
(x, y): (- 2,0)

Answer:

Option B

User Rewind
by
5.8k points